Inv dup del(9p): Prenatal diagnosis and molecular cytogenetic characterization by fluorescence in situ hybridization and array comparative genomic hybridization - Chih-Ping Chen; Yi-Ning Su; Schu-Rern Chern; Chin-Yuan Hsu; Fuu-Jen Tsai; Pei-Chen Wu; Chen-Chi Lee; Yu-Ting Chen; Meng-Shan Lee; Wayseen Wang (Elsevier, 2011)
Objective: To present molecular cytogenetic characterization of prenatally detected inverted duplication and deletion of 9p, or inv dup del(9p). Materials, Methods, and Results: A 35-year-old primigravid woman underwent amniocentesis at 16 weeks of gestation because of advanced maternal age. Amniocentesis revealed a derivative chromosome 9, or der(9) with additional material at the end of the short arm of one chromosome 9. Parental karyotypes were normal. Level II ultrasound showed ventriculomegaly and normal male external genitalia. Repeated amniocentesis was performed at 20 weeks of gestation. Array comparative genomic hybridization revealed a 0.70-Mb deletion at 9p24.3 and an 18.36-Mb duplication from 9p24.3 to 9p22.1. The distal 9p deletion encompassed the genes of DOCK8, ANKRD15, FOXD4, DMRT1, and DMRT3. Fluorescence in situ hybridization analysis using bacterial artificial chromosome clone probes specific for 9p confirmed that the der(9) was derived from the inv dup del(9p). The karyotype of the fetus was 46,XY,inv dup del(9)(:p22.1→p24.3::p24.3→qter)dn or 46,XY,der(9) del(9)(p24.3) inv dup(9)(p22.1p24.3)dn. Polymorphic DNA marker analysis determined a maternal origin of the inv dup del(9p). A 512-g male fetus was subsequently terminated at 22 weeks of gestation with facial dysmorphism. The fetus had normal male external genitalia without sex reversal. Conclusion: Fluorescence in situ hybridization and array comparative genomic hybridization are useful to determine the nature of a prenatally detected aberrant chromosome derived from the inv dup del. Male fetuses with inv dup del(9p) and haploinsufficiency of DMRT1 and DMRT3 may present normal male external genitalia without sex reversal.